Strengthening Small Medium Enterprises (SMEs) towards ASEAN Economic Community - Ardiyansah, Bayu Rian; Hartati, Sri (Journal of Business and Management, 2016)
Abstract- This study addressed the issue of the AEC implementation by researching this topic focused into case study of SMEs ceramic cluster which located in Kiaracondong, Bandung. Purposively, this used aimed to strengthen SMEs toward the AEC implementation. To achieve that aim, this study used qualitative analysis by conducting interview into four SMEs respondents in that cluster. Additionally, this study also interviewed two related government institutions. Initially, this study analyzed the internal firm condition through three components, which are firm performance in the domestic market, awareness and readiness toward AEC, and internationalization drivers and barriers. Then, this study also investigated government roles in supporting SMEs toward the AEC. After analyzing and evaluating internal firm condition and government roles, this study also conducted strategy formulation analysis. This used identified and summarized factors in the previous analysis as the main inputs for the strategy. This study conducted PEST, SWOT, and TOWS analysis. As the results, this study recommended SMEs to focus on actively utilizing internet as direct promotional tools and changing their production process from full manual technique into adapting molding technique. This strategies used to be competitive in the current market. Meanwhile, for the government, this study recommended to focus on facilitating SMEs in developing their management skill and knowledge through intensive trainings evenly.Keywords: SMEs, ASEAN Economic Community, Internal Firm Condition, Government Roles, Strategy Formulation